Conservation area networks for the Indian region: Systematic methods and future prospects - Sarkar, Sahotra; Mayfield, Michael; Cameron, Susan; Fuller, Trevon; Garson, Justin (Himalayan Journal of Sciences, 2008)
We present a framework for systematic conservation planning for biodiversity with an emphasis on the Indian context. We illustrate the use of this framework by analyzing two data sets consisting of environmental and physical features that serve as surrogates for biodiversity. The aim was to select networks of potential conservation areas (such as reserves and national parks) which include representative fractions of these environmental features or surrogates. The first data set includes the entire subcontinent while the second is limited to the Eastern Himalayas. The environmental surrogates used for the two analyses result in the selection of conservation area networks with different properties. Tentative results indicate that these surrogates are successful in selecting most areas known from fieldwork to have high biodiversity content such as the broadleaf and subalpine conifer forests of the Eastern Himalayas. However, the place-prioritization algorithm also selected areas not known to be high in biodiversity content such as the coast of the Arabian Sea. Areas selected to satisfy a 10% target of representation for the complete surrogate set provide representation for 46.03% of the ecoregions in the entire study area. The algorithm selected a disproportionately small number of cells in the Western Ghats, a hotspot of vascular plant endemism. At the same target level, restricted surrogate sets represent 33.33% of the ecoregions in the entire study area and 46.67% of the ecoregions in the Eastern Himalayas. Finally, any more sophisticated use of such systematic methods will require the assembly of Geographical Information Systems (GIS)-based biogeographical data sets on a regional scale. Key words: Indian biodiversity, Eastern Himalayas, complementarity, area prioritization, reserve selection, surrogacy Himalayan Journal of Sciences Vol.4(6) 2007 p.27-40